Improving scalability in loosely structured Peer-to-Peer (P2P) systems - Viray, Ben-Hur C. (2007)
The successes of the early systems such as Napster and Gnutella have shown that peer-to-peer (PSP) can be as powerful as the client-server model in terms of user functionalities. Napster and Gnutella enable users to share files in a peer-to-peer manner. Aside from sharing files, PSP is used for instant messaging and distributed computing. Although P2P has been increasingly used, it has problems with scalability, which is the capability of the network to handle the growing number of peers. Unstructured, structured, and loosely structured frameworks have been applied to P2P systems with varying success to improve scalability for file sharing in the Internet. We have used an approach in unstructured systems and applied it to Harvster, a proposed loosely structured system. This involves the application of Lv's flow of control and topology adaptation for unstructured systems where it controls the arrival and departure of messages and redirects the data flow from one node to another. This redirection is enhanced with replication. NeuroGrid, a Java-based testbed built for the study, design and analysis of P2P systems, is used in this research. The behavior of the new system is analyzed through NeuroGrid's simulation tool and shows marked improvement over existing loosely structured peer-to-peer systems NeuroGrid and Freenet. The experimental results demonstrate the effectiveness of Harvster in the average number of message transfers and nodes reached, which are key elements of scalability and performance.
Thesis (M.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Peer-to-peer architecture (Computer networks).; Computer networks -- Scalability